Analisis Proses Pembuatan Batik Tulis Sukapura Di Desa Janggala Kecamatan Sukaraja Kabupaten Tasikmalaya - Siti Maria Ulfah (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This research aims to find out the preparations for working on Sukapura Handwritten Batik, knowing the marketing process of Sukapura batik products to consumers. The process of making Sukapura batik. The instruments used by researchers in research to collect data are observation, interviews and documentation studies. Data is analyzed through data reduction, data display, conclusions and verification. The findings from this research are that Sukapura written batik has its own uniqueness and characteristics that have been passed down from generation to generation, inherited from previous ancestors. Sukapura batik motifs can be modified and updated according to orders desired by the target market customers.